Pragmatic Study: an Analysis of Form and Function of Arabic Directive Speaking in "the Story' of Imam Hasan Basri RA” Animation / دراسة تداولية: تحليل لشكل ووظيفة أفعال الكلام للتوجيه العربي في الرسوم المتحركة "قصة الإمام الحسن البصري" - Zenylda, Azka (ATHLA : Journal of Arabic Teaching, Linguistic and Literature, 2022)
Pragmatics is one of the branches of linguistics which includes the relationship between outside language and the intent of an utterance, while pragmatics itself is a linguistics study that studies the use of language associated with the context in which it is used. The meaning of the language can be understood if the context is known. This study focuses on one branch of pragmatics, namely Arabic directive speech acts in the animation "The Story of Imam Hasan Al-Bashri ''. This study serves to explain and describe the forms and functions of Arabic directive speech acts in the animation "The Story of Imam Hasan Al-Bashri". The method used by the researcher is a descriptive analysis method. It is carried out through three stages, namely: (1) data collection stage, (2) data analysis stage, (3) data analysis presentation stage. The results of this study indicate that the form of speech acts in the animation "Kisah Imam Hasan Al-Bashri '' consists of: (1) direct speech acts, (2) indirect speech acts, (3) literal speech acts, and (4) speech acts. not literal speech. Meanwhile, the functions of Arabic speech acts in the animation "The Story of Imam Hasan Al-Bashri" include: Requestives directive speech acts, Questions directive speech acts, Requirements directive speech acts, Prohibitives directive speech acts, Permissives directive speech acts, Advisores directive speech acts.